Engaging occupations among persons at risk for stroke: A health paradox. (17th February 2022) - Asaba, Eric; Bergström, Aileen; Patomella, Ann-Helen; Guidetti, Susanne
Abstract: Background: An occupational perspective in stroke prevention could support sustainable changes in habits and routines that could contribute to reduce modifiable risk factors. Aim: To explore engaging occupation in relation to risk for stroke by drawing on experiences from everyday life among persons with a heightened risk for stroke. Material and methods: Interviews from 14 persons with an increased risk for stroke were analysed by a constant comparative approach. Findings: The analysis resulted in the core category; the paradox of engaging occupations and health. The paradox involved aspects of engaging occupations that could provide well-being and at the same time were compromising considering stroke health. Conclusions and significance: The paradox conceptually challenges some of the core values inherent in occupational therapy regarding the relationship between engaging occupations, health and well-being. Gaining a deeper understanding of experiences of occupations and studying this in relation to health promoting or compromising characteristics of occupations, can facilitate lifestyle programs that support changes in everyday life. Moreover, programs need to be designed to offer personal relevance and to facilitate a positive balance between health compromising occupations and health promoting occupations in everyday life.